Protecting honey bees (Apis mellifera) from thermal stress: Probiotics and prebiotics buffer the survival and antioxidant enzyme activity - Rahil Mirabi Moghaddam; Najmeh Sahebzadeh; Ehsan Rakhshani; Naser Tajabadi; Rassol Bahreini (PLoS ONE, 2026)
Environmental temperature profoundly influences honey bee ( Apis mellifera ) physiology, behavior, and survival. In recent years, nutritional interventions have gained attention as potential strategies to mitigate stress-induced physiological disruptions in honey bees. This study evaluated the efficacy of dietary supplementations enriched with combined prebiotics and probiotics in alleviating temperature-related stress. Newly-emerged worker bees were first maintained under optimal conditions (35 °C) and received dietary supplements for 21 days, after which they were exposed to four temperature regimes (4, 15, 35, and 40 °C) to evaluate their stress resilience. Bee survival and the activity of key antioxidant enzymes (i.e., superoxide dismutase, ascorbate peroxidase, catalase, and peroxidase) were assessed. Bees received a commercial probiotic (Progen®) and the prebiotic Inulin in equal proportions at concentrations of 2.5, 5, 7.5, and 10 g L -1 . The results demonstrated that bees exposed to thermal stress and supplemented with the highest combined dose of probiotic and prebiotic (10 g L -1 of each supplement) exhibited significantly higher survival compared with bees receiving lower doses (2.5 g L -1 ), or an unsupplemented diet. In unsupplemented control groups, temperature stress induced marked increases in antioxidant enzyme activities, indicating significant oxidative stress. In contrast, supplementation resulted in a dose-dependent reduction in enzyme activities across all temperatures, strongly suggesting a protective, and stress-buffering effect. These physiological benefits were accompanied by an increase in gut microbial abundance and enhanced indicators of energy metabolism in the supplemented bees. Overall, our findings demonstrated that combined probiotic and prebiotic supplementation can effectively buffer honey bees against temperature-induced physiological stress, highlighting a practical nutritional strategy to enhance colony resilience under the fluctuating environmental conditions associated with seasonal variation and ongoing global climate change.